Peningkatan Impulse Buying Pengguna E-Commerce melalui Diskon Live Streaming Shopping Shopping Lifestyle dan Kemudahan Transaksi - latief, fitriani (Jurnal Manajemen STIE Muhammadiyah Palopo, 2025)
Abstract This study aims to determine the significant positive effect of discounts on impulsive purchases of e-commerce users in Makassar, the significant positive effect of live streaming shopping on impulsive purchases of e-commerce users in Makassar, the significant positive effect of shopping lifestyle on impulsive purchases of e-commerce users in Makassar and the significant positive effect of ease of transaction on impulsive purchases of e-commerce users in Makassar. This study uses a quantitative approach and uses a questionnaire with a Likert scale as a data collection tool. The sample used in this study consisted of 105 respondents who were active e-commerce users in Makassar. The results of the study showed that: there is a significant positive effect between discounts on impulsive purchases of e-commerce users in Makassar, there is a significant positive effect between live streaming shopping on impulsive purchases of e-commerce users in Makassar, there is a significant positive effect between shopping lifestyle on impulsive purchases of e-commerce users in Makassar and there is a significant positive effect between ease of transaction on impulsive purchases of e-commerce users in Makassar. Keywords: discounts, live streaming shopping, shopping lifestyle, ease of transactionsAbstrak Penelitian ini bertujuan untuk mengetahui pengaruh positif signifikan diskon terhadap impulse buying pengguna e-commerce di Makassar, pengaruh positif signifikan live streaming shopping terhadap impulse buying pengguna e-commerce di Makassar, pengaruh positif signifikan shopping lifestyle terhadap impulse buying pengguna e-commerce di Makassar dan pengaruh positif signifikan kemudahan transaksi terhadap impulse buying pengguna e-commerce di Makassar. Penelitian ini menggunakan pendekatan kuantitatif dan menggunakan kuesioner dengan skala likert sebagai alat pengumpulan data. Sampel yang digunakan dalam penelitian ini terdiri dari 105 responden yang merupakan pengguna aktif e-commerce di Makassar. Hasil penelitian menunjukkan bahwa : terdapat pengaruh positif yang signifikan antara diskon terhadap impulse buying pengguna e-commerce di Makassar,Â  terdapat pengaruh positif yang signifikan antara live streaming shopping terhadap impulse buying pengguna e-commerce di Makassar, terdapat pengaruh positif signifikan antara shopping lifestyle terhadap impulse buying pengguna e-commerce di Makassar serta terdapat pengaruh positif yang signifikan antara kemudahan transaksi terhadap impulse buying pengguna e-commerce di Makassar.Kata Kunci: diskon, live streaming shopping, shopping lifestyle, kemudahan transaksi.